SSR markers for a critically endangered species Euryodendron excelsum and a distantly related species Ternstroemia gymnanthera (Ternstroemiaceae). (February 2015) - Cui, Limin; Su, Yingjuan
Abstract: Euryodendron excelsum is a critically endangered tertiary relict plant endemic to China. It has only one population remaining in Ba Jia Zhen of Yangchun, Guangdong. In this study, we discovered 25 microsatellite markers from E. excelsum using a Fast Isolation by Amplified Fragment Length Polymorphism of Sequences COntaining Repeats (FIASCO) protocol. Thirteen loci demonstrated polymorphisms, with the number of alleles per locus ranging from 2 to 13. Values for observed and expected heterozygosity ranged from 0.176 to 1.000 and from 0.261 to 0.889, respectively. Three loci ( ZXM -17, ZXM -54, and ZXM -92) were found to significantly deviate from Hardy-Weinberg equilibrium. In addition, five of 13 loci could be successfully cross-amplified in Ternstroemia gymnanthera . These microsatellite loci may help to further survey the adaptive evolution and genetic variation of E. excelsum for guiding its conservation. Highlights: Thirteen polymorphic microsatellite loci were isolated in Euryodendron excelsum . The genetic characteristics of E . excelsum were evaluated. Five loci were amplified in a distantly related species Ternstroemia gymnanthera . These SSR markers will help to survey adaptive evolution and genetic variation.